A FUNÇÃO SOCIAL DA ESCOLA NO OLHAR DOS DIFERENTES SEGMENTOS DA EQUIPE ESCOLAR - Giannotti, Rosa da Cunha Barbosa (2006)
The objective of this project is to grasp and analyse the various understandings about the social role of the school as well as their relations with the school s project. A survey about the institution evolution along the historical periods is carried out, the school is defined as a space socially destined for the transmission of the knowledge accumulated by the human society for the new generations, it is searched in LIBÂNEO and MIZUKAMI the way to characterize - for each of the pedagogical tendencies/ approaches - their social role at the micro, meso and macro levels and as a kaleidoscopic web of relations . It is searched in Gramsci s thoughts the theoretical references and concepts that enable the reading and the understanding of the analysed elements. Ethnographic qualitative studies were carried out through semi-structured interviews, field observation and documentary analysis. It was verified that the school has a strong traditional liberal and in the non-critical theory tendency characterized by Saviani on its pedagogical project and also in the speeches of the school team. The speeches of the subjects involved in the research (students, parents, collaborators and teachers) bring a strong belief in the school as a socializing organ which enables success and social promotion for the students since it provides the initial education for the job market. The understanding of the social role of the school is not noticed unless from the point of view of the individual interest. As far as it is concerned there is affinity in the expectations among the different segments of the team. Expectations which will hardly be reached due to the reproductive mechanisms of the society that also affect the school life.